Psychological Outcomes and Predictors of Weight Loss in Adolescents With Severe Obesity Following a Reversible Endoscopic Bariatric Procedure - Klemenčič, Simona; Bujišić, Ana; Hribernik, Neža Štiglic; Battelino, Tadej; Homan, Matjaž; Orel, Rok; Kotnik, Primož (Frontiers in Pediatrics, 2021)
Introduction: Adolescent and children obesity is a growing concern worldwide. Bariatric surgery is used as an effective treatment for adolescents with obesity and provides physical and mental health benefits. Application of alternative, minimally invasive, safe and reversible endoscopic procedures, such as the Duodenojejunal bypass liner (DJBL), has been recently suggested as an effective treatment for adolescents with obesity. We explored specific psychological outcomes of adolescents with obesity during a year of follow-up after undergoing a reversible endoscopic bariatric procedure, and a year after removal. We were also interested in identifying psychological factors that could predict successful weight loss after the procedure. Methods: Nine-teen adolescent with severe obesity undergoing DJBL procedure were psychologically assessed in an open-label, prospective clinical trial (NTC0218393), at the implantation of device and at the removal of device after 12 months. Control group of 26 adolescents with severe obesity were recruited from the same outpatient clinic undergoing only conservative treatment. In addition, adolescents from the intervention group were followed for 12 months after the removal of the device. The Youth Self Report (YSR) was used to assess adolescents’ emotional and behavioural problems; The Multidimensional Body-Self Relations Questionnaire (MBSRQ) to assess body image and The Eating Disorder Examination Questionnaire (EDE-Q) to assess attitudes and behaviours related to eating disorder. Results: Significant improvements in somatic complain (p=0.001), emotional and behavioural problems (p=0.011) and food restraining (p = 0.004) were found in the intervention group at device removal compared to the control group. Moreover, at the time of device removal compared to baseline, improvements in several psychological outcomes were found (total problems: p=0.000). Adolescents also became more satisfied with their appearance. Majority of observed changes remained stable at the next follow up a year after the device removal. Significant predictors of successful weight loss at device removal were fewer overeating episodes (B=0.147, p=0.022) lower body satisfaction (B=0.932, p=0.013). Discussion: Following a reversible bariatric procedure, improvements of psychological (emotional and behavioural) factors were found in adolescents with severe obesity. Psychological predictors of successful weight loss were identified, showing the greatest importance of eating behaviour and body satisfaction in successful weigh loss.